2012
DOI: 10.1128/jcm.00131-12
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pseudopneumoniae Identification by Pherotype: a Method To Assist Understanding of a Potentially Emerging or Overlooked Pathogen

Abstract: bThe recent identification of Streptococcus pseudopneumoniae (pseudopneumococcus) has complicated classification schemes within members of the "mitis" streptococcal group. Accurate differentiation of this species is necessary for understanding its disease potential and identification in clinical settings. This work described the use of the competence-stimulatory peptide ComC sequence for identification of S. pseudopneumoniae. ComC sequences from clinical sources were determined for 17 strains of S. pseudopneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 50 publications
(68 reference statements)
4
12
0
Order By: Relevance
“…treptococcus pseudopneumoniae is a recently designated species included in the S. oralis-S. mitis group and closely related to Streptococcus pneumoniae that may be identified using appropriate phenotypic and/or molecular assays (1,8,11,12). Pathogenic significance of S. pseudopneumoniae in respiratory tract diseases is still unclear in spite of its association with both a history of chronic obstructive pulmonary disease (COPD) and exacerbation of COPD (4,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…treptococcus pseudopneumoniae is a recently designated species included in the S. oralis-S. mitis group and closely related to Streptococcus pneumoniae that may be identified using appropriate phenotypic and/or molecular assays (1,8,11,12). Pathogenic significance of S. pseudopneumoniae in respiratory tract diseases is still unclear in spite of its association with both a history of chronic obstructive pulmonary disease (COPD) and exacerbation of COPD (4,6).…”
mentioning
confidence: 99%
“…Species identification was based on optochin (Oxoid Ltd., Basingstoke, England) susceptibility in an ambient atmosphere and resistance or intermediate susceptibility in a 5% CO 2 atmosphere, insolubility in 1% sodium deoxycholate (BD Diagnostics, Heidelberg, Germany), and a positive reaction with the AccuProbe Pneumococcus test (bioMérieux, Marcy l'Etoile, France) (1,6). Despite recent reports recommending molecular methods, such as recA gene sequencing or real-time PCR assays targeting the Spn9802 fragment and the autolysin gene lytA, for accurate identification of S. pseudopneumoniae (8,12), the association of one molecular and two phenotypic assays we used here allowed confident identification, because optochin-resistant or deoxycholate-insoluble S. pneumoniae isolates are rarely observed (as reviewed in reference 10).…”
mentioning
confidence: 99%
“…Despite a previous report that S. pseudo pneumoniae does not have a comC gene [43], we subsequently located this gene from their published genome sequence [50]. In addition, our study found that the comC gene was present in a further 17 clinical strains of the pseudopneumococcus [50].…”
Section: S Pseudopneumoniaementioning
confidence: 55%
“…In addition, our study found that the comC gene was present in a further 17 clinical strains of the pseudopneumococcus [50]. The majority of these pseudopneumococci carried the same pherotype, CSP6.1 [50] that had previously been identified as a rare pneumococcal pherotype [51].…”
Section: S Pseudopneumoniaementioning
confidence: 95%
“…Of these targets, the lytA primer/probe set designed by Carvalho et al (2007) has been tested most extensively in clinical studies (Cvitkovic Spik et al, 2013;Wu et al, 2013). This target has been shown not to cross-react with the recently described species Streptococcus pseudopneumoniae (Arbique et al, 2004), which is genetically very similar to Streptococcus pneumoniae and can be misidentified as atypical pneumococci with traditional identification methods (Leung et al, 2012;Rolo et al, 2013). Many of the other qPCR assays also give a positive result for Streptococcus pseudopneumoniae (Carvalho et al, 2007) and are therefore not specific for Streptococcus pneumoniae.…”
Section: Introductionmentioning
confidence: 99%